Преобразование во вторую гармонику фемтосекундного импульса с центральной длиной волны 950 нм - Алексеев С. В. Сергей Владимирович; Иванов Н. Г. Николай Георгиевич; Лосев В. Ф. Валерий Федорович; Миронов С. Ю. Сергей Юрьевич (2016, 2016)
Заглавие с экрана